Relevance of digital diplomacy in promoting the national interest of states: reflection on Ethiopian case - Misgana Yifiru Ayenew (Cogent Social Sciences, 2024)
The advent of the Internet and social media revolutionized all aspects of human life, and diplomacy has not been unscathed. This is manifested in the creation of a new mode of conducting international relations, which has been described as digital diplomacy. Current diplomatic trends show that digital diplomacy has emerged as a more preferred foreign policy instrument across the world, including in Ethiopia, as it annihilates the spatial and temporal constraints of conventional diplomacy. This study therefore examines the essence of digital diplomacy in the Ethiopian context for communicating the foreign policy objectives of the country. To this end, the study employed both primary and secondary sources, which were collected through semi-structured interviews and a review of relevant archival materials. The findings reveal that recently Ethiopia has been streamlining its diplomacy by integrating e-tools into its diplomatic practice to pursue its national interests, which are democratization, development, and the projection of its national pride and prestige via persuasion and attractiveness. Even though it is not sufficient, by enabling the country to capitalize on soft power in the realms of national image building and public diplomacy, digital diplomacy facilitates the articulation and realization of the country’s foreign policy objectives.